2020
DOI: 10.1039/d0mh00979b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ion transport by graphene oxide/cellulose nanofibers assembled membranes for high-performance osmotic energy harvesting

Abstract: As an emerging potential energy source to address the energy crisis, osmotic energy has attracted increasing attention. Fast ion transport is essential for this blue energy and for other membrane-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 47 publications
5
106
1
Order By: Relevance
“…This could affect the Seebeck coefficient as several studies reported on electric potential difference from water concentration gradient in ionically charged systems 25 and ion concentration difference across ion selective membranes, so called hydrovoltaics. 26 In sealed samples, water cannot evaporate or be absorbed along the temperature gradient, and the measured thermovoltage is caused by the thermodiffusion of ions and water molecules, which is similar for the two gel electrolytes IL-HEC(250k) and IL-HEC(90k). Hence, the observed difference in the apparent Seebeck coefficient comes from another phenomenon than the thermoelectric effect.…”
Section: Resultsmentioning
confidence: 92%
“…This could affect the Seebeck coefficient as several studies reported on electric potential difference from water concentration gradient in ionically charged systems 25 and ion concentration difference across ion selective membranes, so called hydrovoltaics. 26 In sealed samples, water cannot evaporate or be absorbed along the temperature gradient, and the measured thermovoltage is caused by the thermodiffusion of ions and water molecules, which is similar for the two gel electrolytes IL-HEC(250k) and IL-HEC(90k). Hence, the observed difference in the apparent Seebeck coefficient comes from another phenomenon than the thermoelectric effect.…”
Section: Resultsmentioning
confidence: 92%
“…[236][237][238] Wu et al reported the construction of a composite membrane formed by graphene oxide and cellulose nanobers (GO/CNFs). 228 Under optimized conditions and applying a concentration gradient of 50-fold (mimicking seawater/river water), the system exhibited an output power density of 4.19 W m 2 exceeding results obtained with isolated cellulose nanobers and graphene oxide. This enhancement was ascribed to larger interlayer distances that allow fast ion transport and high transmembrane ux but without losing selectivity due to the space charge introduced by CNFs.…”
Section: D-materials Based and Ultrathin Membranes For The Development Of Sge Nanodevicesmentioning
confidence: 86%
“…For some materials, temperature-induced changes in the surface charge which also cause variation in h max have been reported. 175,227,228 As an example, on silica surfaces, an excessive increase in the temperature can result in a drastic diminution in E m and power explained by a reduction in the effective surface charge density owing to the formation of hydrophobic patches that mask the mesoporous surface. 227 An asymmetric temperature conguration in NRED was addressed in detail by Liu and coworkers in their studies based on numerical simulations in cylindrical nanochannels.…”
Section: Temperaturementioning
confidence: 99%
“…When moisture is absorbed, the dissociation and diffusion of ions within the hydrated nanochannels induce the directional movement of charge, producing an open-circuit potential of ~115 mV with a maximum short-circuit current of 45 nA. To harvest osmotic energy, TEMPO-oxidized NFC has been integrated with graphene oxide (GO) nanosheets to form a composite membrane ( Figure 5(l) ) [ 185 ]. The introduction of TEMPO-oxidized NFC enlarges the channel, decreases the energy barrier for ion transport, and provides space charge between the pristine GO nanosheets to maintain the ion selectivity.…”
Section: Nanogenerator Developmentmentioning
confidence: 99%